Wake up, Black Bear! - Bentley, Dawn; Stover, Beth, 1969-; Smithsonian Institution (Norwalk, Conn. : Little Soundprints, 2003)
After a winter of sleeping, Black Bear and her cubs catch fish, eat honey, and climb trees in the spring sunshine.
"Hoppers"--P. [4] of cover.
Presch.-1.
Keywords: Black bear -- Juvenile fiction; Black bear -- Fiction; Bears -- Fiction